2010
DOI: 10.1016/j.plefa.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Early development of essential fatty acid deficiency in rats: Fat-free vs. hydrogenated coconut oil diet

Abstract: This study examined the effects of feeding an essential fatty acid deficient (EFAD) diet either without fat or with added hydrogenated coconut oil (HCO) on fatty acid profiles in rats. Both diets induced equivalent biochemical evidence of EFAD reflected by the triene/tetraene ratio in plasma phospholipids within 2 weeks. However, the HCO diet led to larger increases of 16:1n7 and 18:1n9 in muscle but smaller increases in fat tissue and plasma triglycerides than the fat-free diet, suggesting greater increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Recent evidence has indicated that a diet containing coconut oil as the only source of lipids can increase DHA depletion in the brain when compared to a fat free diet, even for a short term treatment (Ling et al, 2010). In the present study, the diet based on coconut oil and containing a linoleic/a-linolenic acid ratio of 16 resulted in lesser DHA levels ($50%) and increased the contents of some saturated and monounsaturated fatty acids in the midbrain phospholipids.…”
Section: Midbrain Fatty Acid Profilesupporting
confidence: 41%
See 1 more Smart Citation
“…Recent evidence has indicated that a diet containing coconut oil as the only source of lipids can increase DHA depletion in the brain when compared to a fat free diet, even for a short term treatment (Ling et al, 2010). In the present study, the diet based on coconut oil and containing a linoleic/a-linolenic acid ratio of 16 resulted in lesser DHA levels ($50%) and increased the contents of some saturated and monounsaturated fatty acids in the midbrain phospholipids.…”
Section: Midbrain Fatty Acid Profilesupporting
confidence: 41%
“…Considering these neurochemical differences, the present study investigated whether the dopaminergic cells of the SNcv would be more vulnerable than those from the SNrm to the effects of a diet commonly used to induce EFA deficiency, due its reduced levels of both linoleic and a-linolenic acids and high contents of saturated fatty acids (Deuel et al, 1954;Hargrave et al, 2005;Ling et al, 2010). We also investigated whether this dietary treatment over two generations could affect the amount of the dopaminesynthesizing enzyme in the ventral midbrain.…”
Section: Introductionmentioning
confidence: 98%
“…Hepatic weight and TG content were significantly higher in the TFA group than in the control group, which might be caused by a slightly lower intake of dietary essential FAs, especially linoleic acid C18:2 cis . Deficiency or lack of dietary linoleic acid was reported to increase TG accumulation in rat liver 28 . According to other reports 29,30 , the minimal recommended intake of dietary linoleic acid and linolenic acid C18:3 to prevent essential FA deficiency is estimated at approximately 1 and 0.1 0.2 of total energy intake, respectively, in adult humans.…”
Section: Discussionmentioning
confidence: 97%
“…The conclusion that Elovl6 along with SCD1 plays a crucial role in the regulation of 18:1n-9 formation is the same as that of Karahashi et al [37] and Marks et al [38], who showed the role of Elovl6 in the liver of Goto-Kakizaki rats and female rats, respectively. Previous studies demonstrated that fat-free diet feeding resulted in the up-regulation of SCD1 mRNA [39] and in the increase in the proportions of 16:1n-7 and 18:1n-9 in the liver [40]. Therefore, we attempted to compare the effect of clofibric acid treatment with that of fat-free diet feeding on MUFA synthesis in intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%